2012
DOI: 10.1186/1479-5868-9-29
|View full text |Cite
|
Sign up to set email alerts
|

A window of opportunity? Motor skills and perceptions of competence of children in Kindergarten

Abstract: BackgroundOur aim was to examine the relationship between motor skill proficiency and perceptions of competence of children in their first year of school. We also explored gender-based differences.FindingsParticipants were 260 kindergarten children (mean age = 5y 9 m; boys = 52%) from eight schools; representing 78% of eligible children in those schools. Motor skills were measured using the Test of Gross Motor Development-2 and perceptions of physical competence were assessed using the Pictorial Scale of Perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
147
6
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 27 publications
25
147
6
11
Order By: Relevance
“…In terms of gender differentiation, 81.6% of girls scored at or below the 50 th percentile, in comparison to 64% of boys. Generally, these results reflect recent findings about the low level of FMS proficiency in preschool children (Foulkes et al, 2015;Hardy et al, 2009;LeGear et al, 2012). The poor level of FMS proficiency found in our study becomes more important because some studies have found that higher FMS proficiency in childhood results in a higher level of physical activity during adolescence (Barnett et al, 2009;Barnett, van Beurden, Morgan, Brooks, & Beard, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of gender differentiation, 81.6% of girls scored at or below the 50 th percentile, in comparison to 64% of boys. Generally, these results reflect recent findings about the low level of FMS proficiency in preschool children (Foulkes et al, 2015;Hardy et al, 2009;LeGear et al, 2012). The poor level of FMS proficiency found in our study becomes more important because some studies have found that higher FMS proficiency in childhood results in a higher level of physical activity during adolescence (Barnett et al, 2009;Barnett, van Beurden, Morgan, Brooks, & Beard, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Based on these results, the authors suggest that developmentally appropriate interventions should be implemented in preschool settings to promote FMS, with targeted activities for boys and girls. A low level of FMS (16)(17)(18)(19)(20)(21)(22)(23)(24) th percentile range) was also found in a study by LeGear et al (2012), which primarily explored the relationship between the level of motor skills proficiency and the self-perception of competence in 260 Canadian preschoolers. Though the motor skills level was quite low, the children held generally positive perceptions of their physical competence, which provided a window of opportunity for fostering skillfulness (LeGear et al, 2012).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Some [6,7] have found no difference between the locomotor skills of boys and girls, while others [8,9,10] have found girls to be superior. For example, Yang et al [10] found girls to perform better than boys in such skills as galloping, hopping, horizontal jumping, and sliding.…”
Section: Introductionmentioning
confidence: 99%
“…A forma como se percebe produz impactos sobre sua autoconfiança e disposição para novos desafios e aprendizagem. Pessoas que se percebem competentes em suas habilidades tendem a persistir por mais tempo na execução de tarefas e a assumir responsabilidades sobre suas atitudes e conquistas (Valentini, 2002b;LeGear et al, 2012;Nobre, Bandeira, Ramalho, Nobre, & Valentini, 2015). IndivĂ­duos com baixos nĂ­veis de competĂŞncia percebida tendem a evitar tarefas que representem novos desafios, demonstrando falta de interesse na aprendizagem de novas habilidades (Almeida, Valentini, & Berleze, 2009;Valentini, 2002b).…”
Section: Introductionunclassified